It only takes a moment [compact disc, unabridged] - Clark, Mary Jane Behrends (HarperCollins Audio, 2008)
Janie Blake, daughter of KEY News anchorwoman Eliza Blake, has been kidnapped. Everyone seems to be in on the investigation of this high-profile case, but as time goes by and Eliza herself becomes a suspect, she takes matters into her own hands.